PARylation of the forkhead‐associated domain protein DAWDLE regulates plant immunity. (18th October 2016) - Feng, Baomin; Ma, Shisong; Chen, Sixue; Zhu, Ning; Zhang, Shuxin; Yu, Bin; Yu, Yu; Le, Brandon; Chen, Xuemei; Dinesh‐Kumar, Savithramma P; Shan, Libo; He, Ping
Abstract: Protein poly(ADP‐ribosyl)ation (PARylation) primarily catalyzed by poly(ADP‐ribose) polymerases (PARPs) plays a crucial role in controlling various cellular responses. However, PARylation targets and their functions remain largely elusive. Here, we deployed an Arabidopsis protein microarray coupled with in vitro PARylation assays to globally identify PARylation targets in plants. Consistent with the essential role of PARylation in plant immunity, the forkhead‐associated (FHA) domain protein DAWDLE (DDL), one of PARP2 targets, positively regulates plant defense to both adapted and non‐adapted pathogens. Arabidopsis PARP2 interacts with and PARylates DDL, which was enhanced upon treatment of bacterial flagellin. Mass spectrometry and mutagenesis analysis identified multiple PARylation sites of DDL by PARP2. Genetic complementation assays indicate that DDL PARylation is required for its function in plant immunity. In contrast, DDL PARylation appears to be dispensable for its previously reported function in plant development partially mediated by the regulation of microRNA biogenesis. Our study uncovers many previously unknown PARylation targets and points to the distinct functions of DDL in plant immunity and development mediated by protein PARylation and small RNA biogenesis, respectively. Synopsis: Protein poly(ADP‐ribosyl)ation plays crucial roles in various cellular processes, but few PARylation targets have been identified so far in plants. This study reports on a proteome‐wide screen for PARP targets in Arabidopsis and identifies PARylation of DAWDLE as essential for its function in plant immunity. The forkhead‐associated (FHA) domain protein DAWDLE (DDL) positively regulates plant immunity. Biochemical and genetic analyses indicate that PARylation of DDL is required for its function in pathogen defense. PARylation of DDL is not essential for its function in plant development. Abstract : Protein poly(ADP‐ribosyl)ation plays crucial roles in various cellular processes, but few PARylation targets have been identified so far in plants. This study reports on a proteome‐wide screen for PARP targets in Arabidopsis and identifies PARylation of DAWDLE as essential for its function in plant immunity.